The Development and Experimental Analysis of Freestanding Single‐Walled Carbon Nanotube/Sulfur Composite Cathode for the Next Generation of Sulfur‐Based Batteries - Kiai, Maryam Sadat; Aslfattahi, Navid; Karatas, Deniz; Baydogan, Nilgun; Samylingam, Lingenthiran; Kadirgama, Kumaran; Kok, Chee Kuang (Wiley, 2025)
This work uses a solution‐based and scalable method to provide a freestanding single‐walled carbon nanotube (SWCNT)/S cathode in both LiS and NaS batteries. SWCNTs with high conductivity and surface area can enhance the cathode flexibility. The incorporation of oxygen and sulfur bonds can enhance active redox sites for chemical adsorption. Sulfur and oxygen effectively hinder the shuttle effect by improving chemical interactions between the polysulfides and the nonpolar carbon framework, leading to improved cyclability of NaS and LiS cells. The cycling stability plots of NaS and LiS batteries with freestanding SWCNT/S as a cathode are investigated for 150 cycles at a high current density of 1000 mA g−1. Both cells display a stable capacity behavior during cycling. The discharge capacity of the LiS cell with the SWCNT/S cathode is retained at 978.2 mAh g−1 while the NaS cell only shows the capacity retention of 769.4 mAh g−1 after 150 cycles. Coulombic efficiencies of ≈94% and 90% are observed for LiS and NaS cells respectively. Therefore, the SWCNT/S cathode in both LiS and NaS batteries hinders the polysulfide shuttle, providing high electrolyte diffusion, resulting in improved active material reutilization and minimized capacity fading. Freestanding SWCNT/S cathode can enhance cycling stability over long‐term cycling and is proved to be a promising cathode in both LiS and NaS batteries.